Chitosan nanoparticles from marine squid protect liver cells against N-diethylnitrosoamine-induced hepatocellular carcinoma. (1st September 2017) - Subhapradha, Namasivayam; Shanmugam, Vairamani; Shanmugam, Annaian
Highlights: Chitosan nanoparticles from gladius of marine squid Sepioteuthis lessoniana were analyzed. The effect of both pre-treatment and post-treatment of chitosan nanoparticles against NDEA induced HCC were determined. The protective effect of chitosan nanoparticles on hepatic cells was investigated. Results confer the anti-oxidative and anti-lipidemic property of chitosan nanoparticles. Findings established that chitosan nanoparticles had potential prevention of HCC. Abstract: Rationale of this study was framed to investigate the protective effect and anti-cancer property of nanoparticles based on chitosan isolated from squid, Sepioteuthis lessoniana, on hepatic cells in N -Nitrosodiethylamine-induced hepatocellular carcinoma in rats. The results conferred that the chitosan nanoparticle supplementation had a protective effect on liver cells by reducing the levels of marker enzymes and bilirubin and thus increasing the albumin levels. The level of reduced glutathione, ascorbic acid and α-tocopherol significantly increased in both post- and pre-treatment with chitosan nanoparticles. The levels of antioxidant enzymes were enhanced and lipid peroxidation products were diminished while treating nitrosodiethylamine-induced hepatocellular carcinoma with chitosan nanoparticles. Supplementation of chitosan nanoparticles had potent anti-hyperlipidemic property that was evidenced by monitoring the serum lipid levels and its components. Animals pre-treated with chitosan nanoparticles along with nitrosodiethylamine showed a significant reduction in the total cholesterol and triglycerides levels with increase in the levels of phospholipids and free fatty acids. Chitosan nanoparticles treated rats showed significant increment in high-density lipoprotein cholesterol and reduction in low-density lipoprotein and very low-density lipoprotein cholesterol when compared with levels in nitrosodiethylamine-induced hepatocellular carcinoma. Nitrosodiethylamine-induced carcinoma changes on circulation and hepatic antioxidant defense mechanism were regulated by chitosan nanoparticles, concluding that the chitosan nanoparticles have a potent protective effect on liver cells which might be due to its robust antioxidant and anti-lipidemic property.